Large effect of phosphate-solubilizing bacteria on the growth and gene expression of Salix spp. at low phosphorus levels - Koczorski, Piotr; Furtado, Bliss Ursula; Baum, Christel; Weih, Martin; Ingvarsson, Pär; Hulisz, Piotr; Hrynkiewicz, Katarzyna (Frontiers in Plant Science, 2023)
Phosphorus (P) is one of the most important nutrients required for plant growth and development. However, owing to its low availability in the soil, phosphorus is also one of the most difficult elements for plants to acquire. Phosphorus released into the soil from bedrock quickly becomes unavailable to plants, forming poorly soluble complexes.PhosphorusPhosphate-solubilizing bacteria (PSB) can solubilize unavailable phosphoruscontaining compounds into forms in which phosphorus is readily available, thus promoting plant growth. In this study, two willow species, Salix dasyclados cv. Loden and Salix schwerinii × Salix viminalis cv. Tora, were inoculated with two selected bacterial strains, Pantoea agglomerans and Paenibacillus spp., to evaluate the plant growth parameters and changes in gene expression in the presence of different concentrations of tricalcium phosphate: 0 mM (NP), 1 mM (LP), and 2 mM (HP). Inoculation with PSB increased root, shoot and leaf biomass, and for the HP treatment, significant changes in growth patterns were observed. However, the growth responses to plant treatments tested depended on the willow species. Analysis of the leaf transcriptomes of the phosphate-solubilizing bacteriuminoculated plants showed a large variation in gene expression between the two willow species.For the Tora willow species, upregulation of genes was observed, particularly for those involved in pathways related to photosynthesis, and this effect was strongly influenced by bacterial phosphorus phosphate solubilization. The Loden willow species was characterized by a general downregulation of genes involved in pathway activity that included ion transport, transcription regulation and chromosomes. The results obtained in this study provide an improved understanding of the dynamics of Salix growth and gene expression under the influence of PSB, contributing to an increase in yield and phosphorus-use efficiency.